ChemInform Abstract: Two Modifications of (TeO)(HAsO4) and Its Dehydration Product (Te3O3)(AsO4)2 — Three More Examples of Tellurium(IV) with a Fivefold Oxygen Coordination. Issue 16 (22nd April 2014) - Weil, Matthias
Abstract Two modifications of (TeO)(HAsO4) are prepared by reactions of TeO2 with aqueous H3AsO4.